Natural form sculpture in Nongrawiang forest - Srihad, Theerapong (Journal of Fine and Applied Arts Khon Kaen University, 2022)
The purpose of this series of creations is to study, experiment and create sculptures from nature, life and time. It is an important ingredient in the creation of sculpture. Nature and environment the passage of time causing non-stop is constantly changing represents the relationship between people and the environment both body and mind express feelings by using shapes that are characterized by their structure, life with volume. To create visual effects and to realize the coexistence of life structures using different materials, clay and iron and mixed together into new components. It presents a view of life in nature that depend in harmony with each other. Can develop further patterns and concepts in creativity the sculpture works of the researcher and the impact on students, teachers, artists and contemporary art circles of Thailand continue to.